Literary Translation
XVII, 264 p.
Keywords: Literary Translation: Redrawing the Boundaries is a collection of articles that gathers together current work in literary translation to show how research in the field can speak to other disciplines such as cultural studies, history, linguistics, literary studies and philosophy, whilst simultaneously learning from them.